Relationship between wheat yield and area under the disease progress curve of leaf rust - Tavella, Cayo Mario; Sonego, Olavo Roberto (Pesquisa Agropecuaria Brasileira, 2014)
The yield reduction caused by leaf rust on wheat was studied in relation to the area below the disease progress curve (ABC), and disease readings in various growth stages of the host, using data from a series of experiments established to test chemicals for rust control. Trials were carried out at Indápolis, MS. Brazil, during three years. Regression was studied, being the equation obtained with the area below the curve of disease progress as the independent variable, the one which explained a greater portion of the variation in yield, in two of three cases.